EFEFCT OF KAOLIN ON GROWTH AND CLINICAL SIGNS IN COMMON CARP EXPOSED TO COPPER SULPHATE TOXICITY - Abdulmotalib J. Al-Rudainy; N. M. Salman; S.A. Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate the effect of kaolin on growth and clinical signs in Cyprinus carpio exposed to copper sulphate. For this rationale, six treatment groups with two replicates were used in this experiment as follows: C- served as control negative group without exposed to kaolin or CuSO4; C+ served as control positive group was exposed to 0.91mg/l CuSO4 only; T1, T2, T3 and T4 were subjected to 0.91mg/l of CuSO4 and kaolin was added to them at levels of 2, 4, 6 and 8 g/l respectively. Result findings reveal a positive relationship of the mean total weight gain among treatments T1, T2, T3 and T4 with the increase in the percentage of kaolin, practically in T4 which reached 13.2g. The mean daily weight gain of the experimental fish ranged between – 0.08 g/day/fish in C+ treatment to 0.55g/day/fish in C- treatment. C- treatment recorded the best value for feed conversion ratio and feed conversion efficiency with values ​​of 3.5 and 28.57% respectively, followed by T4 with values ​​of 3.9 and 25.0% respectively. In addition, values ​​of the relative growth rates fluctuated between the lowest value in C+ treatment (-2.50%) and the highest value in C- treatment (18.34%). Specific growth rate, experienced the same previous pattern as they ranged between – 0.04 and 0.24%/day in C+ and C- treatments respectively. These results suggested that kaolin helped to reduce the toxicity of copper sulphate in experimental fish.